Computing Characterizations of Drugs for Ion Channels and Receptors Using Markov Models - Tveito, Aslak; Lines, Glenn T. (Springer Nature, 2021)
Computational Science and Engineering; Biomedicine general; Computer Imaging, Vision, Pattern Recognition and Graphics